A REVIEW ON DISINTEGRATION CONTROL MATRIX TABLETS - Kanke, Pralhad K.; Sawant, Pankaj; Jadhav, Ajit; Usman, Md. Rageeb Md.; Jain, Bharat V. (Journal of Drug Delivery and Therapeutics, 2018)
A number of sustained release formulations are available in the market which successfully sustained the drug release over a prolonged period of time by different mechanisms. The new approach for sustaining the drug release is disintegration control matrix tablet which sustained the drug release up to 24hrs by controlling the disintegration rate of tablet. Disintegration control matrix tablet (DCMT) mainly forms the granules containing drug and disintegrating agent such as low substituted hydroxyl propyl cellulose by various methods such as solid dispersion technique. The sustained release of drug is maintained by increasing the wax coating or decreasing the amount of disintegrants. The release of drug from tablet is uniform throughout till all the drug releases from tablet as it involves drug release by diffusion, dissolution and surface erosion mechanism. DCMT increases the solubility of drug and improves the bioavailability without disturbing gastrointestinal transit. BCS Class II, III, IV drugs are the best candidate for DCMT formulations. Keywords: Disintegration control matrix tablet (DCMT), Wax, Disintegrating agent, Solid dispersion.